Assessing Lower Limb Proprioception in Diabetic Neuropathy: Challenges and Methods - Sudheera Kunduru; Muthukumaran Jothilingan; Pravin Aaron; Prathap Suganthirababu; J Akbar; Smita E. Joseph (Journal of Pharmacy and Bioallied Sciences)
Background: Diabetic peripheral neuropathy often leads to loss of joint position sense, distal weakness, and an increased risk of falls. Since proprioception and somatosensory information from the feet are essential for balance and gait control, assessing lower limb proprioception is crucial in understanding the impact of neurological conditions, injuries, and aging on mobility and quality of life. However, evaluating proprioceptive function in the lower limbs remains challenging due to the complexity of sensory-motor integration. Objectives: This review discusses various methods for assessing lower limb proprioception, such as joint position sense, kinaesthesia, and force sense tests, while addressing their limitations. It also explores challenges in clinical practice, including individual variability, task complexity, and psychological influences. Results: The findings suggest the integration of innovative technologies like wearable sensors and virtual reality, as well as the development of standardized protocols. Implication: Results suggest that by adapting these technologies, assessment accuracy and advance research and clinical practice in proprioception can be improved.